INITIAL IDENTIFICATION FOR DEVELOPMENT VALUE CO-CREATION TRIADIC BUSINESS MODEL INNOVATION: THE CASE OF MALANG COFFEE INDUSTRY - Suryadi, Nanang; Anggraeni, Rila; Permadi, Fajar (Jurnal Aplikasi Manajemen, 2020)
This study aims to identify the relationship between the three actors (triadic) in creating value in the coffee industry in Malang. The relationship in the coffee industry involves suppliers (coffee farmers), sellers (coffee shops), and consumers. The expected novelty and technological breakthrough is the development of Value Co-Creation Triadic Business Model Innovations. This business model innovation is based on a collaborative and innovative process of creating, delivering, and capturing value (value co-creation) by involving 3 (three) main actors in the coffee industry. This business model innovation can be used as a foundation to create value propositions and revenue streams for actors in the coffee product value chain to face and win the competition. Besides, it will increase the role of coffee as one of the agricultural products that will be the leverage of the Indonesian economy.